Answer:
g(n) = - 19 + (n - 1)*6
Step-by-step explanation:
The way to do this is to try a couple and then see if you can make some sort of equation that follows the rule.
g(1) = - 19
=============
g(2) = g(2 - 1) + 6
g(2) = g(1) + 6
g(2) = -19 + 6
g(2) = -13
=============
g(3) = g(2) + 6
g(3) = -13 + 6
g(3) = - 7
==========
g(4) = g(3) + 6
g(4) = - 7 + 6
g(4) = - 1
==========
g(5) = 5
g(6) =11
===========
Now the hard part. You have to start with - 19
The nth term is g(n) = - 19 + (n - 1)*6
Now see if it works.
g(7) = - 19 + (7 - 1)*6
g(7) = - 19 + 6 * 6
g(7) = -19 + 36
g(7) = 17
Is that correct?
g(7) = g(n - 1) + 6
g(7) = g(6) + 6
g(7) = 11 + 6
g(7) = 17 Seems to be the same as the explicit formula gives.
7 strawberries. 30 plus 12 is 42. 42 divided by 6 equals to seven. 7 strawberries each.
Answer: $9,500
Step-by-step explanation:
It asks how much in interest not the total value
Answer: sooo ok i see here that it might be 5 inches if i'm wrong correct me
Step-by-step explanation: